Hypomelanosis in chickens - Marco, Heather Gaile (Division of Cell Biology, 2018)
Hypomelanosis, a severe reduction in pigmentation, is a widespread phenomenon which affects many different vertebrate species, including humans and chickens. The cause(s) of various forms of hypomelanosis is (are) not known. The aim of this study was to determine the cause of hypomelanosis in a breed of white chickens (White Plymouth Rock x Pile Game). It was hoped that this hypomelanotic breed may provide insight into the etiopathogenesis of certain human hypomelanotic disorders, such as vitiligo and albinism. To determine whether melanocytes are present in the hypomelanotic skin, two melanocyte-specific assays were carried out, in situ DOPA histochemistry and a sensitive radiometric assay for tyrosinase. The results show that active tyrosinase was present in 8, 9 and 10 day skins. However, unlike normal black skin, the level of tyrosinase did not increase with age, suggesting that the melanocytes either die or that they do not continue to synthesise tyrosinase. Ultrastructurally, these melanocytes appeared to be morphologically normal and they did not show signs of premature degeneration. Unlike black chick melanocytes, however, they contained very few premelanosomes and fully melanised melanosomes were never observed, suggesting that hypomelanosis results from the arrested development (melanisation) of melanosomes in vivo. Two different experiments were carried out to determine whether this blockage in melanogenesis is intrinsic in the melanocyte or whether it is caused by extrinsic environmental factors. The outcome of these studies were conflicting: 1) In culture, white chick neural crest cells produced pigment, suggesting that the melanocyte is not defective. However, ultrastructural examination of these cultured melanocytes showed that they contained a large proportion of partially melanised melanosomes. 2) Black chick neural crest cells migrated into white skin explants and contributed towards pigment in the developing feathers, suggesting that the white chick tissue environment is also not defective. The results hint that hypomelanosis in the white chicks is caused by the interaction of at least two genetic defects: an intrinsic mutation of the melanocyte, as well as an extrinsic mutation in the melanocyte environment that, in combination, exert an inhibitory influence on melanin synthesis. This study shows that, in situ, white chick melanocytes share some features with ty-pos albino melanocytes and may be representative of this pigmentary disorder. White Plymouth Rock x Pile Game chicks may also be useful as a model for the multi-faceted disorder, vitiligo.